2023
DOI: 10.1037/dev0001557
|View full text |Cite
|
Sign up to set email alerts
|

Testing the whole number interference hypothesis: Contributions of inhibitory control and whole number knowledge to fraction understanding.

Abstract: The present study tests two predictions stemming from the hypothesis that a source of difficulty with rational numbers is interference from whole number magnitude knowledge. First, inhibitory control should be an independent predictor of fraction understanding, even after controlling for working memory. Second, if the source of interference is whole number knowledge, then it should hinder fraction understanding. These predictions were tested in a racially and socioeconomically diverse sample of U.S. children (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 80 publications
0
5
2
Order By: Relevance
“…However, in this study, performance in incongruent and congruent trials was averaged; thus, this null result may be explained by the lack of relation between inhibitory control and congruent trials typically reported in other papers (e.g., Abreu-Mendoza et al, 2020;Coulanges et al, 2021;Gomez et al, 2015). More recently, Leib et al (2023) found that among third-to-seventh graders, inhibitory skills, assessed with a Color-Word Stroop task and a letter Flanker task, contribute to both, congruent and incongruent fraction comparison problems. Similarly, Van Hoof et al (2021) showed a similar cognitive cost in switching from misleading to consistent than when switching from consistent to misleading problems.…”
Section: Contributions Of Executive Functioning To Fraction Knowledgecontrasting
confidence: 52%
See 3 more Smart Citations
“…However, in this study, performance in incongruent and congruent trials was averaged; thus, this null result may be explained by the lack of relation between inhibitory control and congruent trials typically reported in other papers (e.g., Abreu-Mendoza et al, 2020;Coulanges et al, 2021;Gomez et al, 2015). More recently, Leib et al (2023) found that among third-to-seventh graders, inhibitory skills, assessed with a Color-Word Stroop task and a letter Flanker task, contribute to both, congruent and incongruent fraction comparison problems. Similarly, Van Hoof et al (2021) showed a similar cognitive cost in switching from misleading to consistent than when switching from consistent to misleading problems.…”
Section: Contributions Of Executive Functioning To Fraction Knowledgecontrasting
confidence: 52%
“…Overall, the current and past results suggest that fraction learning may be better captured by non-linear, categorical transitions, rather than continuous, cumulative changes. Consistently, cross-sectional data show that at the group level, the degree of use of some comparison strategies decreases with age (e.g., whole-number bias), while more sophisticated yet flawed ones (e.g., reversed bias and gap thinking) increase (González-Forte et al, 2023;Leib et al, 2023). However, only longitudinal designs combined with person-oriented approaches could allow us to describe how students transition from one category to another and whether there are students who may be at a higher risk of stagnation.…”
Section: High School Students' Fraction Comparison Strategy Profilesmentioning
confidence: 63%
See 2 more Smart Citations
“…This finding is aligned with our hypothesis and also contributes to the prior literature by employing a domain-specific measure of inhibitory control (Numerical Stroop). Greater inhibitory control may be particularly beneficial in the context of fraction arithmetic as this cognitive skill may enable individuals to "overcome" the whole-number bias by helping them inhibit whole number strategies that are largely automatized due to the extensive experience individuals have with whole numbers (Siegler et al, 2011;Fitzsimmons et al, 2020b;Leib et al, 2023). Indeed, when dealing with fractions, generalizing some whole-number strategies can be counterproductive.…”
Section: Discussionmentioning
confidence: 99%